Dynamic and Physical Processes Associated with Orographic Precipitation in a Conditionally Unstable, Low-cape and High-speed Wind - Gökhan Sever; Yuh-Lang Lin (Geography, Earth Science and Environment: Research Highlights Vol. 4, 2025)
Orographic effects on precipitation in a conditionally unstable, low convective available potential energy (CAPE), and high-speed wind are investigated by a series of systematic two- and three-dimensional idealized numerical experiments. Sensitivity experiments are performed with a flow with low CAPE to assess the evolution of orographic precipitation in an environment similar to that observed in tropical cyclones, which, unexpectedly, show that precipitation is nearly doubled compared to that with high CAPE. The heavy rain production in the low CAPE case is explained by the following microphysical processes: (1) warm-rain formation processes (auto-conversion and accretion) are more effective, and (2) strong downdraft and advection-induced evaporation tend to deplete precipitation before reaching the ground, which overcomes the intense rain production via graupel and snow melting in high CAPE case. Overall, both in 2D and 3D high-wind simulations, the pattern of the precipitation distribution resembles the bell-shaped mountain profile with the maximum located over the mountain peak, which may be applicable to climate prediction of orographic precipitation.